Síntese e modificação química de biodiesel para formação de epóxidos e carbonatos cíclicos com potencial biodegradabildade - Paiano, Murillo da Silva [UNESP] (2015)
The chemical modification of biodiesel has been an interesting proposal for obtaining various oleochemical compounds with similar porperties and aplications to petroleum derivates, with the difference of being obtained through clean and environmentally benign routes, using natural feedstock as vegetables oil and carbon dioxide, according to several principles of Green Chemistry. This work proposes to conduct a series of chemical modifications of flaxseed biodiesel, from its synthesis, epoxidation and cycloaddtion of CO2 to obtain biodegradable epoxides and cyclic carbonates. The flaxseed biodiesel was produced through Lewis acid catalysis (NbCl5) and had its unsaturation content concentrated by urea purification. The epoxidation of the concentrated biodiesel had its kinetics monitored by the evolution of oxygen oxirane value and studied by GC-FID and GC-MS. The cyclic carbonates were obtained from the solventless cycloaddition of supercritical CO2 in the opoxides catalyzed by TEAB, and have shown good reactants for a wide range of amines to from its respective carbamates (urethanes). FT-IR and NMR (1H and 13C) spectra identified the transformatios of all maior functional groups proving successful in the proposed chemical modifications